login
A370346
Expansion of g.f. A(x) satisfying 1 - Sum_{n>=1} Product_{k=1..n} (x^(2*k-1) - 3*A(x)) = Product_{k>=1} (1 - x^(2*k)) * (1 + x^k - 3*A(x))^2 / (1 + x^(2*k) - 3*A(x))^2.
4
1, 4, 30, 275, 2799, 30436, 346319, 4072754, 49109383, 603892942, 7544208882, 95478830462, 1221573723875, 15773909948027, 205307054116726, 2690677001032332, 35476776659831511, 470270121135358061, 6263499157608619009, 83779630339128146106, 1124938556977304225153, 15157622439788012559209
OFFSET
1,2
COMMENTS
Compare to identity: 1 + 2*Sum_{n>=0} x^(n^2) = Product_{n>=1} (1 - x^(2*n)) * (1 + x^n)^2 / (1 + x^(2*n))^2.
LINKS
FORMULA
G.f. A(x) = Sum_{n>=0} a(n)*x^n satisfies the following formulas.
(1) B(x) = Product_{k>=1} (1 - x^(2*k)) * (1 + x^k - 3*A(x))^2 / (1 + x^(2*k) - 3*A(x))^2.
(2) B(x) = 1 - Sum_{n>=1} Product_{k=1..n} (x^(2*k-1) - 3*A(x)).
(3) B(x) = 3 - Sum_{n>=0} x^(n^2) / Product_{k=0..n} (1 + 3*x^(2*k)*A(x)).
(4) B(x) = 1 - (x - 3*A(x))/(1 + F(1)), where F(n) = -(x^(2*n+1) - 3*A(x))/(1 + (x^(2*n+1) - 3*A(x)) + F(n+1)), a continued fraction.
a(n) ~ c * d^n / n^(3/2), where d = 14.458907819153377265491543116275493396... and c = 0.046179270774970711082728047566196279... - Vaclav Kotesovec, Feb 27 2024
EXAMPLE
G.f.: A(x) = x + 4*x^2 + 30*x^3 + 275*x^4 + 2799*x^5 + 30436*x^6 + 346319*x^7 + 4072754*x^8 + 49109383*x^9 + 603892942*x^10 + 7544208882*x^11 + 95478830462*x^12 + ...
By definition, A = A(x) allows for the following expressions to equal
B(x) = 1 - (x - 3*A) - (x - 3*A)*(x^3 - 3*A) - (x - 3*A)*(x^3 - 3*A)*(x^5 - 3*A) - (x - 3*A)*(x^3 - 3*A)*(x^5 - 3*A)*(x^7 - 3*A) - (x - 3*A)*(x^3 - 3*A)*(x^5 - 3*A)*(x^7 - 3*A)*(x^9 - 3*A) + ...
B(x) = (1 - x^2)*(1 + x - 3*A)^2/(1 + x^2 - 3*A)^2 * (1 - x^4)*(1 + x^2 - 3*A)^2/(1 + x^4 - 3*A)^2 * (1 - x^6)*(1 + x^3 - 3*A)^2/(1 + x^6 - 3*A)^2 * (1 - x^8)*(1 + x^4 - 3*A)^2/(1 + x^8 - 3*A)^2 * ...
where B(x) begins
B(x) = 1 + 2*x + 6*x^2 + 48*x^3 + 431*x^4 + 4350*x^5 + 47112*x^6 + 534852*x^7 + 6280806*x^8 + 75657236*x^9 + 929649564*x^10 + 11607031548*x^11 + 146829845214*x^12 + ...
PROG
(PARI) {a(n) = my(A=[0, 1]); for(i=1, n, A=concat(A, 0);
A[#A] = -polcoeff( ( 1 - sum(m=1, #A, prod(k=1, m, x^(2*k-1) - 3*Ser(A)) ) - prod(m=1, #A, (1 - x^(2*m))*(1 + x^m - 3*Ser(A))^2/(1 + x^(2*m) - 3*Ser(A))^2 ) )/3, #A-1)); H=A; A[n+1]}
for(n=1, 30, print1(a(n), ", "))
CROSSREFS
KEYWORD
nonn
AUTHOR
Paul D. Hanna, Feb 16 2024
STATUS
approved